ASSESSING THE EFFECTIVENESS OF LIQUORICE ROOT EXTRACT LOLLIPOP IN REDUCING THE S.MUTANS COUNT IN SALIVA IN CHILDREN AGED 6-12 YRS-A PILOT STUDY - DR.JYOTSNA SRINATH; DR.GARGI.S; DR.VICTOR SAMUEL (International Journal of Pharma and Bio Sciences, 2015)
To determine the effectiveness of Liquoirce root extract lollipops in reducing the S.mutans count in the saliva of children aged 6-12 yrs using both Culture plating method and Dentocult. Study design; Pilot study Methods; Supervised administration of Liquorice root extract lollipops was given twice daily for 10 days to 10 children aged 6-12 yrs in a primary school setting. Baseline counts and the post intervention counts were compared using Culture plating methods and Dentocult method. Statistics were carried out using non parametric analysis. Results; The post intervention counts when compared to baseline values showed a significant reduction in the S.mutans colonies. Conclusion; Liquorice promises a simple yet effective caries prevention method for high risk children. But further studies need to be carried out in a larger group of population.